Freedom of creation lighting objects using rapid prototyping - Antero Cunha (2007)
RP technologies allow the manufacture of prototypes that can be used as concept,functional or technical models. These prototypes are a precious support for new productsdevelopment. Nowadays, Rapid Prototyping (RP) technologies are considered more mature, and theRapid Manufacturing (RM) concept is becoming progressively more reliable and employed indifferent areas. RM is also an additive process that creates directly the final product without theneed of production tools.Two Product Design students, during their training in INEGI, developed 3 original lamps toillustrate the potentialities, in terms of freedom of creation and manufacturing speed, of using thesetechnologies. Different RP processes, LOM, SLA and SLS, were employed to illustrate possibilitiesto directly create personalized final products. The RP equipments are presently available in Portugaland can be used by particulars or companies that need to develop new products.